Kabar Gembira (Busyrâ) dalam Perspektif Al-Qur’an: Analisis Penafsiran Wahbah Az-Zuhaili Tentang Kata Busyrâ dalam Al-Qur’an - Muhidin SM; Abd. Muid Nawawi; Nurbaiti Nurbaiti (Jurnal Riset Rumpun Agama dan Filsafat, 2023)
One thing that will not be separated from the understanding of Muslims is about the news of joy in the perspective of the Qur'an. Belief in the Islamic world about the existence of the news of gelmbira in the perspective of the Qur'an will demand the existence of relevant interpretation and deep understanding. The purpose of this study is to understand and analyze the contents of the Qur'an related to suluk suluk, as well as identify appropriate research methods to perform the interpretation of the Qur'an. This research is expected to provide a more mendai understanding. The method in this study uses the approach of the library (library research) and research tafsir Al-Qur'an. Literature research is carried out by collecting and analyzing various relevant literary sources, such as the books of tafsir Al-Qur'an by salaf and khalaf scholars, such as Tafsir Ibnul Jarir at-Tabari, Tafsir Jalalayn, Tafsir al-Qurtubi, Tafsir Ibnul Kathsir. The results showed that there are two groups in the context of Busyra, namely Muslims and kafirs. Muslims who obey Allah and do righteous deeds are promised good news (busyrâ) in the form of Allah'S Paradise. But those who disbelieve and do not worship Him will also be given the good news (bulsyrâ) berulpa punishment from Allah SWT.